Formation Of Students' Character Through Islamic Education - Slamet Pamuji; Yadi Mulyadi (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
This article aims to discuss the role of Islamic Education in schools in forming the character of students. Islamic Education is one of the main pillars of character education. Because the role of Islamic Education is important for students. Character education will grow well if students are instilled with religious values properly. Islamic Education material is one of the supports for character education through learning Islamic Education for students where Aqidah is taught as a religious basis, and the Koran and Hadith are taught as life guidelines for students. Fiqh is taught as a legal guide in worship, as well as telling and pursuing the history of the Islamic religion as an exemplary life as well as pursuing morals in students aimed at guiding behavior in carrying out an action whether it is good or not. Therefore, the main aim of learning religious education Islam is the formation of personality in students which can be seen from the behavior and thought patterns of students in their daily lives. Apart from that, it is a successful learning of Islamic Education where the application and learning methods are carried out appropriately and appropriately.